FAKTOR RISIKO COMPUTER VISION SYNDROME PADA MAHASISWA JURUSAN ILMU KOMPUTER FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS LAMPUNG - Debby Cinthya Damiri Valentina; M Yusran; Riyan Wahyudo; Rani Himayani (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2019)
ABSTRACT Introduction: Computer vision syndrome (CVS) is a syndrome that occur due to excessive interaction with computers. Individual, environmental, and computer related risk factors increase CVS prevalence and cause eyes, visual, and extraocular related symptoms. This research aims to observe the relation between risk factors and CVS prevalence in students of Computer Science Major of Mathematics and Natural Sciences Faculty of Lampung University. Method: This research was an analitic survey with cross sectional study. Samples consisted of 56 students of 2014-2016 class year using proportional stratified random sampling techniques. This research used questionnaires and direct measurement of eyes distance and angle gaze of respondents. Collected datas then were analyzed by using univariate and bivariate analysis. Result: The prevalence of CVS obtained from samples was 39 students (69,6%). Statistic tests between risk factors and CVS are listed as follow, gender (p=0,909 OR=1,069), working years (p=0,007 OR=6,188), daily duration of computer exposures (p=0,022 OR=7,708), wearing spectacles (p=0,043 OR=8,000), taking a break (p=0,111 OR=2,786), eyes distance (p=0,028 OR=3,750), and angle gaze (p=0,047 OR=5,000). Conclusion: The significantly related risk factors to CVS were working years, daily duration of exposures, wearing spectacles, eyes distance, and angle gaze towards computer monitors. Keywords: computer vision syndrome, risk factors